Aspirasi Tuntutan Pemekaran Wilayah di Kota Medan - SABARIAH BANGUN (Universitas Sumatera Utara, 2013)
This is a study about regional partition. Especially about aspirations about regional partition in Medan City. As known, in the year 2011 there is discourse about the formation of the Medan Utara City in Medan City. This idea was reported in various media. Interestingly this idea received from various community. This study analyzes the background of the aspirations of the regional partition. Analysis method is using qualitative analysis. This study found that in the case in Medan City, the aspiration about regional partition motivated by a variety of things. One of them is the economic background. There are economic disparities in the core area of the city and the suburbs. In addition there is also a background of the interests of local elites. However local ethnic interests is not raised it is because the area is not the area where the majority ethnic settled. This illustrates that the expansion aspirations based on facts that can be measured.Keywords: Regional partition, economic disparities, local elite.